Mitochondrial Dysfunction Causes Oxidative Stress and Tapetal Apoptosis in Chemical Hybridization Reagent-Induced Male Sterility in Wheat - Wang, Shuping; Zhang, Yingxin; Song, Qilu; Fang, Zhengwu; Chen, Zheng; Zhang, Yamin; Zhang, Lili; Zhang, Lin; Niu, Na; Ma, Shoucai; Wang, Junwei; Yao, Yaqin; et al. (Frontiers in Plant Science, 2018)
Male sterility in plants has been strongly linked to mitochondrial dysfunction. Chemical hybridization agent (CHA)-induced male sterility is an important tool in crop heterosis. Therefore, it is important to better understand the relationship between mitochondria and CHA-induced male sterility in wheat. This study reports on the impairment of mitochondrial function duo to CHA-SQ-1, which occurs by decreasing cytochrome oxidase and adenosine triphosphate synthase protein levels and theirs activities, respiratory rate, and in turn results in the inhibition of the mitochondrial electron transport chain, excessive production of reactive oxygen species (ROS) and disruption of the alternative oxidase pathway. Subsequently, excessive ROS combined with MnSOD defects results in damage to the mitochondrial membrane, followed by ROS release into the cytoplasm. The microspores underwent severe oxidative stress during pollen development. Furthermore, chronic oxidative stress, together with the overexpression of type II metacaspase, triggered premature tapetal apoptosis, which resulted in pollen abortion. Accordingly, we propose a metabolic pathway for mitochondrial-mediated male sterility in wheat, which provides information on the molecular events underlying CHA-SQ-1-induced abortion of anthers and may serve as an additional guide to the practical application of hybrid breeding.